Customer Preferences and Satisfaction Analysis of Video Conference Application for Productive Activities Using Kano Model - Yansen Theopilus; Michael Purwoko (Jurnal Rekayasa Sistem & Industri, 2021)
The rapid development of communication technology and the increasing need for long-distancecommunication in the Covid-19 pandemic era have made video conferencing applications play a vital rolein human productive activities, such as working, studying, doing hobbies, and more. The increasing needhas spurred video conferencing application providers to increase customer satisfaction so that it remainsthe first choice for the customers. To win the competition in this sector, video conferencing applicationproviders should understand and provide the application design that provides maximum satisfaction to thecustomers. Therefore, this study aims to analyze customer preferences and satisfaction with the designattributes of the video conference applications which refers to the three most popular video conferencingapplications in Indonesia: Zoom, Google Meet, and Skype. This study used the Kano Model to identifycustomer preference and satisfaction with the 46 identified design attributes of the video conferencingapplication. The Kano Model analysis used quantitative and qualitative approaches to produce the priorityof importance for each design attribute based on customer preferences and the impact of each attribute oncustomer satisfaction. Based on the Kano Model resulted, there are 19 attractive attributes, 1 must-beattribute, 15 one-dimensional attributes, and 9 indifferent attributes. We also obtained the best proposed design attributes where 37 attributes refer to the Zoom application, 6 attributes refer to the Google Meetapplication, and 3 attributes refer to the Skype application. This study contributes to helping videoconferencing application providers to develop their products better as well as being a reference for thosewho want to develop new video conferencing applications that can satisfy customers well. This study alsohas an impact as a reference in evaluating consumer satisfaction on video conferencing applications inIndonesia.